(untitled) (Applied Biological Research, 2025)
This study evaluated the antioxidant and anti-inflammatory properties of Cleistanthus collinus leaf, bark, and fruit extracts prepared using methanol, ethyl acetate, chloroform, petroleum ether, and water. Antioxidant activity was determined through DPPH, FRAP, H₂O₂ scavenging, metal chelating, and reducing power assays, alongside quantification of total phenolic and flavonoid contents. Anti-inflammatory activity was assessed by albumin denaturation inhibition, anti-proteinase activity, and hypotonicity-induced hemolysis assays. Among the extracts, the methanolic fruit extract exhibited the highest phenolic content (253.1 mg GAE g⁻¹) and showed the most potent antioxidant effects, with IC₅₀ values of 271.69 ± 0.65 μg mL⁻¹ (DPPH), 284.41 ± 2.61 μg mL⁻¹ (H₂O₂ scavenging), and 305.94 ± 1.72 μg mL⁻¹ (metal chelating). Bark methanolic extract showed strong activity in the FRAP assay (IC₅₀ = 363.80 ± 4.04 μg mL⁻¹), while leaf methanolic extract contained the highest flavonoid content (164.65 mg RU g⁻¹). The fruit methanolic extract also demonstrated the strongest anti-inflammatory effect, with hemolysis inhibition reaching 30.21%. These findings highlight the therapeutic potential of C. collinus extracts as natural sources of antioxidants and anti-inflammatory agents.